Length-weight relationship and condition factor of Tilapia (Coptodon zillii) from four water bodies in Kano State, Nigeria - Abdullahi M. Usman; Ibrahim O. Suleiman; Yusuf Garba; Lukman O. kareem; Usman S. Halidu; Hadiza Salihu (The Proceedings of the Nigerian Academy of Science, 2025)
Understanding the growth pattern of fish populations is a key in aquaculture production programme. Twenty-four (24) Coptodon zillii sample were collected from each of the four water bodies (Bagwai dam (BG), river Dundurun Gaya (DG), Tiga dam (TG) and Thomas dam (TD)) to assess its growth pattern variation in a semi-arid region as a guide for breeding and conservation programme. The fish samples were sourced from fishermen landings on the river of each location. Length (L) and weight (W) of all fish sample from each location were measured using standard methods. The statistical relationship between these parameters of Coptodon zillii was established by using the equation: W=aLb, While the condition factor was calculated using K = 100(W/L3). The results revealed that Coptodon zillii exhibited allometric positive growth pattern in TG, negative allometric growth pattern in BG and DG, and isometric growth pattern in TD. The r2 values were generally higher, ranging from 0.901-0.987, revealed a high degree of positive correlation, while the condition factor ranges 1.57-1.86 across the four locations. Coptodon zillii of Thomas dam (TD) exhibited isometric growth pattern, had the highest r2 values and highest condition factor. The fish populations were in good health condition in the four water bodies. Coptodon zillii of Thomas dam (TD) were in the best health condition, and Thomas dam (TD) is the best habitat for Coptodon zillii. Management strategies in Kano state water bodies should be improved for sustainable fish production. More researches are still required on genetic identification, nutrition and economic feasibility to enhance pisciculture in Kano state water bodies. It is recommended for future studies to include other species of tilapia in Kano State water bodies.